2019
DOI: 10.1039/c9ra01521c
|View full text |Cite
|
Sign up to set email alerts
|

EDTA-bonded multi-connected carbon-dots and their Eu3+ complex: preparation and optical properties

Abstract: EDTA-bonded multi-connected carbon-dots (EDTA-C-dots) were prepared from carbon dot precursors and complexed with Eu 3+ to give Eu 3+ -coordinated EDTA-bonded multi-connected carbon dots (Eu-EDTA-C-dots). Whereas EDTA-C-dots were readily soluble in DMSO, Eu-EDTA-C-dots could not be easily dissolved in DMSO, water, or other common organic solvents. The newly prepared materials were thoroughly characterized. The X-ray diffraction results showed that no crystalline phase of Eu oxides (europium oxide or europium h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It is well known that C-dots exhibit weak oxidation or reduction because they can act as both excellent electron acceptors and electron donors. 31,[44][45][46][47] Recently, using Cdots as a catalytic reductant and capping agent, Wang et al have successfully prepared stable silver nanoparticles (Ag NPs). † 46 Since the plasmon absorption of Ag NPs appears mainly in the wavelength range of 350-500 nm, there exists not only electron transfer but also FRET behavior between C-dots and Ag NPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that C-dots exhibit weak oxidation or reduction because they can act as both excellent electron acceptors and electron donors. 31,[44][45][46][47] Recently, using Cdots as a catalytic reductant and capping agent, Wang et al have successfully prepared stable silver nanoparticles (Ag NPs). † 46 Since the plasmon absorption of Ag NPs appears mainly in the wavelength range of 350-500 nm, there exists not only electron transfer but also FRET behavior between C-dots and Ag NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The precursor carbon dots (CDs) were prepared from citric acid and ethylenediamine in an autoclave, and the details can be found in the supporting information. † 31,38 Subsequently, Cuchlorophyllin-bonded carbon dots (denoted as CCPh-CDs) were synthesized as follows: (1) Cu-chlorophyllin (270.0 mg), S-NHS (800.0 mg) and EDC (350.0 mg) were dissolved in 60 mL DMSO at room temperature with stirring; (2) the CDs (500.0 mg) were added into the solution with stirring for 24 hours under light-proof condition; (3) the obtained solution was washed and centrifuged with ethanol for three times; (4) the solid product was vacuum-dried for 10 hours at 40 C and the CCPh-CD1 (Cu 2+ content: 1.21 wt%) has been synthesized.…”
Section: Preparation Of Cu-chlorophyllin-bonded Cdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands around 1640 and 1400 cm À1 are attributed to asymmetrical and symmetrical stretching of the carboxylate (-COO) group. 54 The appearance of these IR bands conrms the presence of EDTA in the NaCeF 4 :Tb 3+ and NaCeF 4 :Tb 3+ /Eu 3+ nanocrystals.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…It has been widely accepted that there are direct energy transfers from CNDs to Eu 3+ /Tb 3+ , which were preliminarily postulated from the observation of CNDs luminescent quenching upon introducing Eu 3+ . [51][52][53][54] In 2011, Zhao et al reported the quenching effect and decreased lifetime of CNDs upon the addition of Eu 3+ . They attributed this phenomenon to the disruption of the radiative recombination on CNDs surface induced by Eu 3+ , with possible charge-or energy transfer process.…”
Section: Mechanisms Of Energy Transfer In Re-cndsmentioning
confidence: 99%